Avaliação do teste bovigam TM na dosagem de interferon gama para diagnóstico da tuberculose bovina - Luciano Bastos Lopes (2003)
This study demonstrates the correlation between the test of interferon gamma (INF ) and tuberculin intradermal tests in the diagnosis of bovine tuberculosis in Brazilian conditions. Centre and two animals from four dairy herds in the state of Minas Gerais tuberculinazados way and the results were then compared with the gamma interferon test. For detection of INF , we used a commercial ELISA kit, BOVIGAM . The results showed no significant differences between the frequencies of animals according to positive and negative intradermal tuberculin test compared intercom and testing range on day zero and within 72 hours after inoculation of tuberculin. The agreement between the test ranged from 79.4% to 85.3% according to the Kappa test. There were no significant differences between mean values of optical densities between the two collection days.